Understanding Learning in Virtual Worlds - Childs, Mark.; Peachey, Anna.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Since the publication of the companion volume Researching Learning in Virtual Worlds in 2010, there has been a growth not only in the range and number of educational initiatives taking place in virtual worlds, but also in the depth of analysis of the nature of that education. Understanding Learning in Virtual Worlds reflects those changes through a collection of chapters that are extended versions of research presented at the second Researching Learning in Virtual Environments conference (ReLIVE 11), an international conference hosted by the Open University UK. Included in this book are chapters that explore the philosophical and methodological underpinnings of understanding learning in virtual worlds, identify and analyse the factors that support learning in these environments, and present case studies that demonstrate some of the various ways in which virtual worlds can be applied to facilitate learning and teaching. The links between learning in a virtual world and learning in the physical world are made apparent throughout, and the authors reveal how understanding learning in one informs the other. Understanding Learning in Virtual Worlds is an important book not only to those who teach in virtual worlds, but to anyone for whom understanding learning, in all its forms, is of interest.
Editors$1 (BIntroduction -- An Alternative (to) Reality -- Guidelines for Conducting Text Based Interviews in Virtual Worlds -- Designing for Hybrid Learning Environments in a Science Museum: Inter-professional Conceptualisations of Space -- An Examination of Student Engagement, Knowledge Creation and Expansive Learning in a Virtual World -- The Strength of Cohesive Ties: Discursive Construction of an Online Learning Community -- +SPACES: Serious Games for Role-Playing Government Policies -- Avatars, Art and Aspirations: The Creative Potential for Learning in the Virtual World -- Second Language Acquisition by Immersive and Collaborative Task-based Learning in a Virtual World -- Do Virtual Worlds Support Engaging Social Conferencing?.s
Keywords: Computer science; Ontology; Social sciences -- Data processing; Information systems; Education; Computer Science; User Interfaces and Human Computer Interaction; Computers and Education; Educational Technology; Computer Appl. in Social and Behavioral Sciences; Computer Appl. in Arts and Humanities; Ontology